Acute myeloid leukaemia: an unusual cause of biliary strictures. Issue 3 (14th March 2019) - Beck, Adele; Hunter, Hannah; Jackson, Simon; Sheridan, David
Abstract : A 17-year-old man with no significant past medical history presented with a 2-week history of worsening jaundice, lethargy, anorexia and progressive right upper quadrant abdominal pain. There were no stigmata of chronic liver disease. Initial investigations were suggestive of cholangitis with large intrahepatic and extrahepatic bile duct strictures but otherwise normal hepatic and splenic appearances. A percutaneous transhepatic cholangiogram with the positioning of drains was performed to alleviate the obstructive jaundice. Within 2 weeks of the first presentation, full blood count revealed a significantly raised white blood count and a subsequent peripheral blood smear and bone marrow were consistent with a diagnosis of acute myeloid leukaemia. Chemotherapy was started after partial improvement of his obstructive jaundice. Complete morphological and cytogenetic remission was obtained 4 weeks after the first cycle of chemotherapy (half dose of daunorubicin and full dose of cytarabine, treated off trial) on control bone marrow. The patient remains in remission.